Design and investigation of dual-guided optical fiber with 60 OAM and 6 LP modes for ultra-high optical communication - Md. Mehedi Hassan; Muhammad Shahin Uddin; Mst. Nargis Aktar; Monir Morshed; Kawsar Ahmed; Bikash Kumar Paul; Md. Sarwar Hossain Mollah (Discover Applied Sciences)
Abstract In this study, a novel photonic crystal fiber with dual-guided areas over the O+E+S+C+L band is proposed, supporting numerous OAM and LP modes for optical communication. The Finite Element Method based COMSOL Multiphysics package was used to investigate its optical features, with anisotropic perfectly matched layers as boundary conditions. Silicon and Schott sulfur hexafluoride (SF6) glass serve as background and ring-core materials, respectively, ensuring high optical transmittance. The fiber demonstrates excellent signal propagation characteristics, such as ERIDs of all hybrid modes exceeding 10–3, reducing mode coupling, and ensuring stable OAM mode transmission. Additional benefits include high mode quality, ultra-large negative dispersion, low confinement loss, and high isolation parameters. Thus, this fiber is a strong candidate for ultrafast optical communication and devices requiring OAM and LP modes. Successful fabrication and installation could herald a new era of flawless optical communication.